2002
DOI: 10.1002/ijc.10214
|View full text |Cite
|
Sign up to set email alerts
|

No mutations in the BACH1 gene in BRCA1 and BRCA2 negative breast‐cancer families linked to 17q22

Abstract: Dear Sir,At least 10% of all breast cancer is estimated to result from an inherited predisposition. 1 Mutations in 2 genes, BRCA1 and BRCA2, have been shown to confer a very high risk for breast and ovarian cancer. 2 A significant proportion of familial cases, however, cannot be attributed to BRCA1 or BRCA2 mutations, 3,4 and additional breast cancer susceptibility gene(s) may account for a fraction of high-risk families. Recently, it was suggested that a novel protein, BACH1, a member of the DEAH helicase fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
21
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 10 publications
9
21
1
Order By: Relevance
“…Several subsequent studies screened the BRIP1 coding sequence in large numbers of BRCA1/2 negative familial breast cancer families from populations in Northern Europe (Luo et al, 2002;Karppinen et al, 2003;Vahteristo et al, 2006), North America (Rutter et al, 2003) and Australia (Lewis et al, 2005). This resulted in the detection of one frameshift mutation and several missense mutations, none of which segregated with breast cancer in the families.…”
Section: Breast Cancermentioning
confidence: 99%
“…Several subsequent studies screened the BRIP1 coding sequence in large numbers of BRCA1/2 negative familial breast cancer families from populations in Northern Europe (Luo et al, 2002;Karppinen et al, 2003;Vahteristo et al, 2006), North America (Rutter et al, 2003) and Australia (Lewis et al, 2005). This resulted in the detection of one frameshift mutation and several missense mutations, none of which segregated with breast cancer in the families.…”
Section: Breast Cancermentioning
confidence: 99%
“…Previous studies have analyzed potential associations between BRIP1 variants and breast cancer risk, either by mutation analysis or by genotyping, to select single nucleotide polymorphisms (SNPs) within the gene (Lei and Vorechovsky, 2003;Rutter et al, 2003;Sigurdson et al, 2004;Lewis et al, 2005;Garcia-Closas et al, 2006;Vahteristo et al, 2006). Although the rs2048718 (5ꞌ-untranslated region, UTR), rs4988345 (exon 15), and rs4986764 (exon 18) polymorphisms have been previously examined in the context of breast cancer, these genetic association studies have failed to produce consistent results (Luo et al, 2002;Lei and Vorechovsky, 2003;Song et al, 2007;Pabalan et al, 2013). Furthermore, several important SNPs, such as rs2048718, rs4986764, rs4986763, rs11079454, and rs7213430, have not been included in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Three samples with both germline and tumor DNA were available and were analysed by PCR-SSCP as described previously. 10 The rare 517T allele was retained in tumors of all 3 cases and no obvious allelic imbalance or loss of heterozygosity was observed in any of these samples (data not shown).…”
Section: Dear Sirmentioning
confidence: 86%
“…However, a follow-up study reported no mutations in the germline of 29 multiple-case breast cancer families with positive nonparametric linkage scores to short tandem repeats flanking the BACH1 locus at 17q and of 95 unrelated individuals with familial breast cancer who had no detectable mutation in BRCA1 and BRCA2. 10 The latter study reported a 517C3 T transition on 5 of 1,586 chromosomes in the Swedish population (allelic frequency 0.3%), leading to a substitution of arginine (R) 173 for cysteine (C) in a putative nuclear localization sequence (NLS) of BACH1. 10 NLS is a short peptide sequence necessary and sufficient for nuclear localization of a protein, 11 and single amino acid substitution involving critical residues in NLS has been shown to impair the nuclear localization.…”
Section: Dear Sirmentioning
confidence: 97%
See 1 more Smart Citation